2011
DOI: 10.1614/ipsm-d-10-00013.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Native Desert Plants with Red Brome (Bromus rubens): Toward Identifying Invasion-Reducing Species

Abstract: The interactions between native and exotic species occur on a continuum from facilitative to competitive. A growing thrust in invasive species science is differentiating where particular native species occur along this continuum, with practical implications for identifying species that might reduce the invasibility of ecosystems. We used a greenhouse experiment to develop a competitive hierarchy of 27 native species with red brome, an invasive annual grass in the arid lands of the southwestern United States, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Positive interactions in arid environments can also have indirect effects that are nontrophic on the annual plant community (Lortie et al ., ). Invasion by non‐natives is increasingly becoming a critical issue even in relatively high‐stress ecosystems (Rodríguez‐Buriticá & Miriti, ; Abella et al ., ). Moreover, there is an increasing need to consider multiple factors when modeling interactions of native and exotic species with climate variation (Preston et al .…”
Section: Discussionmentioning
confidence: 97%
“…Positive interactions in arid environments can also have indirect effects that are nontrophic on the annual plant community (Lortie et al ., ). Invasion by non‐natives is increasingly becoming a critical issue even in relatively high‐stress ecosystems (Rodríguez‐Buriticá & Miriti, ; Abella et al ., ). Moreover, there is an increasing need to consider multiple factors when modeling interactions of native and exotic species with climate variation (Preston et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Abella ; Abella et al . ). It has generally been thought resistance to invasion and resilience from fire (Brooks & Chambers ) were lowest in mid‐elevation areas in the Mojave Desert because biophysical conditions were the most favourable for invasive grasses (Brooks & Matchett , Brooks, Minnich & Matchett in press).…”
Section: Introductionmentioning
confidence: 97%
“…Munro), non-native forbs or native forbs (Brooks 1999). Many studies in the Mojave Desert have shown abundance of both native and non-native vegetation changes after fire and also vary with time since fire, sometimes resulting in communities once dominated by native woody shrubs being converted to ones where herbaceous species, and especially invasive grass, either dominate or are a much greater part of the community than prior to burning (Callison, Brotherson & Bowns 1985;Minnich 1995;Lei 1999;Brooks & Matchett 2003, 2006Webb et al 2003;Abella 2009;Abella et al 2011). It has generally been thought resistance to invasion and resilience from fire (Brooks & Chambers 2011) were lowest in mid-elevation areas in the Mojave Desert because biophysical conditions were the most favourable for invasive grasses (Brooks & Matchett 2006, Brooks, Minnich & Matchett in press).…”
Section: Introductionmentioning
confidence: 99%
“…3a), and actually had higher biomass when grown in combination than when grown alone, suggesting this species was facilitated by growing in a diverse community. Other studies have also found that A. tessellata was robust to exotic competition (Brooks 2009;Abella et al 2011), potentially due to traits such as large seed size and early-season germination (Salo et al 2005). Hence, A. tessellata could be an effective choice for restoration efforts attempting to establish native cover via seeding, especially when there may be potential competition from exotic species present in the seedbank.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have also found that A . tessellata was robust to exotic competition (Brooks ; Abella et al ), potentially due to traits such as large seed size and early‐season germination (Salo et al ). Hence, A .…”
Section: Discussionmentioning
confidence: 99%